BUSINESS CONTINUITY WITH BUDI, KNOWLEDGE AND HIKMAH - Suhaimi Mhd Sarif; Yusof Ismail; Dolhadi Zainudin (Journal of Islamic Management Studies, 2022)
Business continuity enables the longevity of business enterprises. Business enterprises relied on financial and competitive advantage factors for business continuity. Budi is in the mind, feeling and action for betterment. Knowledge enables skill and ability. Budi hikmah integrates mind, soul, action, knowledge, skill and ability with Tawhidic paradigm to contribute to the well-being and mercy of the world. This research explores the influence of budi, knowledge and hikmah on business continuity through personal interviews with owners of business enterprises. The informants argued that the influence of budi, knowledge and hikmah on business continuity occurred through operational relationship, social cognitive relationship, hybrid of competition-business intelligence, hybrid of operational, social and reflection with new insights and synergy to the budi-knowledge-wisdom relationships. The hybrid relationship is attributed to participation, level of interactions, and capability. The budi-knowledge-hikmah enables systematic business continuity.